Trade restrictions are the wrong way to address food supply issues in the COVID-19 crisis - Glauber, Joseph W. (Capitol Hill Publishing Corp., 2020)
The COVID-19 pandemic has caused many disruptions in the food distribution systems, ranging from health issues in meat and other food processing plants to impacts of lockdown procedures that have disrupted food chain flows. The resulting disruptions to the food supply chain are borne by consumers in the form of shortages and higher retail prices. They are also affecting many farmers and ranchers who are facing lower farm gate prices and must manage increasing inventories of animals and some crops because of sharply curtailed access to food away from home marketing channels that serve restaurants and institutional buyers such as schools.